Pengaruh Pembayaran Elektronik, Estetika Desain dan Promosi terhadap Kepuasan Pelanggan di Tataring Cafe & Resto - Ano Victory Sinaga; Hilma Harmen (Lembaga Yasin AlSys, 2026)
Customer satisfaction is an important aspect of culinary business sustainability, especially in facing changes in consumer behavior that are increasingly influenced by the convenience of digital transactions, the attractiveness of spatial design, and promotional strategies. This study aims to examine the effects of electronic payment, design aesthetics, and promotion on customer satisfaction at Tataring Cafe & Resto. This study used a quantitative approach with an ex post facto method. The research sample consisted of 50 respondents selected through saturated sampling. Data were collected using a Likert-scale questionnaire and then analyzed using multiple linear regression through the t-test, F-test, and coefficient of determination. The results of the study show that electronic payment has a positive and significant effect on customer satisfaction, with a calculated t-value of 4.138 and a significance value of < 0.05. Design aesthetics also had a positive and significant effect, with a calculated t-value of 14.366 and a significance value of < 0.05. In addition, promotion had a positive and significant effect, with a calculated t-value of 3.581 and a significance value of < 0.05. Simultaneously, electronic payment, design aesthetics, and promotion had a positive and significant effect on customer satisfaction, with a calculated F-value of 264.413 and a significance value of < 0.05. These three variables were able to explain 81.3% of the variation in customer satisfaction at Tataring Cafe & Resto. The conclusion of the study affirms that the convenience of electronic payment, attractive design aesthetics, and effective promotion are important factors in increasing customer satisfaction. The implications of this study provide practical contributions for culinary business managers in designing service, spatial design, and promotional strategies that are more responsive to customer needs.